2007
DOI: 10.1007/s11060-007-9421-4
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces G2/M cell cycle arrest in a p53-dependent manner and upregulates ING4 expression in human glioma

Abstract: Gliomas are the most common and lethal primary tumors of the central nervous system (CNS). Despite current rigorous treatment protocols, effect of chemotherapy has failed to improve patient outcome significantly. Curcumin is a potent antioxidant that possesses both anti-inflammatory and anti-tumor activities, can suppress the initiation, promotion, and metastasis of different tumors. Its anti-tumor properties in various cancer models and negligible toxicity in normal cells make it a promising chemotherapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
101
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(111 citation statements)
references
References 37 publications
6
101
0
4
Order By: Relevance
“…The molecular mechanism of renal cell carcinoma has been extensively investigated, but there is no targeted therapy owing to a lack of targets. As ING4 was downregulated, or even mutated, in multiple cancer types (8,15,16), In the present study, ING4 was inferred to be associated with multiple cancer types, potentially making it an ideal target for cancer therapy. In the present study, the level of ING4 mRNA and protein was probed in renal cancer tissue specimens in 125 patients with CCRC, and the adjacent normal tissue from 40 patients were used as a control.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…The molecular mechanism of renal cell carcinoma has been extensively investigated, but there is no targeted therapy owing to a lack of targets. As ING4 was downregulated, or even mutated, in multiple cancer types (8,15,16), In the present study, ING4 was inferred to be associated with multiple cancer types, potentially making it an ideal target for cancer therapy. In the present study, the level of ING4 mRNA and protein was probed in renal cancer tissue specimens in 125 patients with CCRC, and the adjacent normal tissue from 40 patients were used as a control.…”
mentioning
confidence: 55%
“…In addition, ING4 altered apoptosis, contact inhibition and DNA repair (9,10). ING4 has been considered as an important tumor suppressor gene, whose expression was significantly downregulated in a number of malignant tumors, including breast cancer, glioma and lung cancer (8,11,12). However, the expression of ING4 has not been investigated in renal cell carcinoma.…”
mentioning
confidence: 99%
“…Recently Aggarwal and co-workers using a commercially available curcumin mix reported that different analogs of curcumin present in turmeric showed variable anti-inflammatory and antiproliferative activities (Sandur et al, 2007). Curcumin or diferuloylmethane, a major component present in turmeric is a powerful antioxidant and is linked with the suppression of mutagenesis, inhibited nuclear factor-K B (NF-K B) activation, suppressed cyclin D1 and antiapoptotic gene products, induced cytochrome C release, activated caspases and have anti-angiogenic effects through down-regulation of vascular endothelial growth factor (VEGF) (Choudhuri et al, 2005;Aggarwal et al, 2006;Aggarwal et al, 2007;Liu et al, 2007;Shankar & Srivastava, 2007). Curcumin is currently in clinical trials for treatment of various cancers (Sharma et al, 2004;Garcea et al, 2005;Dhillon et al, 2006;Rafailov et al, 2007) and for Alzheimer's disease (Yang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Surajit and colleagues demonstrated the activity of curcumin by inducing receptor-and mitochondria-mediated apoptotic pathways (15,16). Besides the apoptotic pathway, Liu and colleagues claimed that curcumin exerts cancer resistance not through apoptosis but through arrest of the cell cycle at the G2/M phase and is mediated by up-regulation of p53 (8). Nevertheless, in this study, we explored the anti-cancer mechanism not only for apoptosis, but also documented the most prevalent genetic aberrance of GBM.…”
Section: Discussionmentioning
confidence: 99%
“…In malignant brain tumors, curcumin also exhibits its pleiotropic activity, which includes inducing cell cycle arrest at the G2/M stage through up-regulation of ING4, suppressing tumor growth by inhibition of AP-1 and NF-κB, and inhibiting anti-apoptotic signaling by increasing the Bax to Bcl-2 ratio (7)(8)(9). Nevertheless, most failure of cancer therapy in clinical practice is attributed to the polymorphism of cancer cells.…”
Section: Introductionmentioning
confidence: 99%